Towards the stereoselective synthesis of bicyclic and tricyclic alkaloid natural products - Patcharaporn Sae-Lao (2012)
In this thesis we discuss the stereoselective synthesis of natural products containing bicyclic heterocycle with a bridgehead nitrogen atom. The unique structural feature of this core skeleton has inspired interest regarding to their stereochemistry and biological properties.